2016
DOI: 10.3109/13880209.2015.1137601
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of ellagic acid against animal models of scopolamine- and diazepam-induced cognitive impairments

Abstract: (2016) Beneficial effects of ellagic acid against animal models of scopolamine-and diazepam-induced cognitive impairments, Pharmaceutical Biology, 54:10, 1947-1953, DOI: 10.3109/13880209.2015 PHARMACEUTICAL BIOLOGY, 2016 VOL. 54, NO. 10, 1947-1953 http://dx.doi.org/10.3109/13880209.2015 Context In a previous study, it has been shown that ellagic acid (EA), a polyphenolic compound found in pomegranate and different berries, prevents cognitive and hippocampal long-term potentiation (LTP) impairments induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Ellagic acid (E) is a naturally occurring phenolic compound found in grapes, nuts, strawberries, raspberries, green tea, pomegranates, as well as royal jelly and honey . Ellagic acid has received considerable attention because of its extensive array of biological properties including potent antioxidant, antiapoptotic, antiinflammatory, cardioprotective, ulcer healing, antifibrotic, antidiabetic, hypolipidemic, and antiatherosclerotic properties …”
Section: Introductionmentioning
confidence: 51%
“…Ellagic acid (E) is a naturally occurring phenolic compound found in grapes, nuts, strawberries, raspberries, green tea, pomegranates, as well as royal jelly and honey . Ellagic acid has received considerable attention because of its extensive array of biological properties including potent antioxidant, antiapoptotic, antiinflammatory, cardioprotective, ulcer healing, antifibrotic, antidiabetic, hypolipidemic, and antiatherosclerotic properties …”
Section: Introductionmentioning
confidence: 51%
“…More pharmacokinetic studies of EGA are needed to elucidate the differential actions of EGA and urolithins. One of the scientific reports in the literature suggested that EGA can have neuroprotective potential [12] and it is supposed to enhance cholinergic function and prevent long-term potentiation deficits in different brain regions of rats [13,14]. These studies made us to propose the positive impact of EGA in the management of dementia of SAD type.…”
Section: Ellagic Acid Administration Negated the Development Of Strepmentioning
confidence: 98%
“…Of particular interest for this study is the reported ability of EA to lower the rotenone-induced generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in PC12 cells [22] as well as its ability to exhibit a neuroprotective effect against oxidative damage in diabetic rats by suppressing oxidative stress [23]. From cognitive and behavioral points of view, EA prevents scopolamine-and diazepam-induced cognitive impairments [24,25] and may be of potential benefit in brain stroke by alleviating the oxidative stress characteristic for this condition [26]. Data also supports EA's brain-protective properties against 6-OHDA-induced neuroinflammation in rats as well as cognitive and long-term potentiation deficits following traumatic brain injury [27].…”
Section: Introductionmentioning
confidence: 99%